The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/eci.12885
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and age‐related arterial stiffness in women with systemic lupus erythematosus

Abstract: The results of this study suggest that cardiorespiratory fitness might attenuate the age-related arterial stiffening in women with systemic lupus erythematosus and might thus contribute to the primary prevention of cardiovascular disease in this population. As the cross-sectional design precludes establishing causal relationships, future clinical trials should confirm or contrast these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This increase in fitness is clinically relevant since a 1-MET increase is associated with a 13% to 15% reduction in CV and all-cause mortality [51], and with 10% to 30% lower adverse cardiovascular event rates [25]. Moreover, higher cardiorespiratory fitness has been shown to be related to a lower CV risk in patients with rheumatoid arthritis [52] and with lower age-related arterial stiffness in SLE [20], indicating that future studies should address the impact of long-term changes in cardiorespiratory fitness on CV health in SLE and other rheumatic populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in fitness is clinically relevant since a 1-MET increase is associated with a 13% to 15% reduction in CV and all-cause mortality [51], and with 10% to 30% lower adverse cardiovascular event rates [25]. Moreover, higher cardiorespiratory fitness has been shown to be related to a lower CV risk in patients with rheumatoid arthritis [52] and with lower age-related arterial stiffness in SLE [20], indicating that future studies should address the impact of long-term changes in cardiorespiratory fitness on CV health in SLE and other rheumatic populations.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Sports Medicine (ACSM) highlights the need to undertake a minimum of 150 min/week (i.e., accumulated in bouts of ≥10 min) of aerobic exercise of moderate to vigorous intensity in adults [18]. In a sample of women with SLE with mild/inactive disease, we cross-sectionally observed no association between accelerometer-assessed physical activity and arterial stiffness [19], although a higher level of cardiorespiratory fitness was related to lower age-related arterial stiffness in this population [20]. Although aerobic exercise has a promising role attenuating arterial stiffness in the general population [21], its effects in women with SLE have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should characterize the association of physical fitness with arterial stiffness in patients with SLE. Preliminary research from our group suggests that higher cardiorespiratory fitness could attenuate the age-related arterial stiffness in women with SLE [ 42 ]. Clinical trials should also address the extent to which meeting the minimum amount of aerobic exercise might positively influence arterial stiffness this population.…”
Section: Future Researchmentioning
confidence: 99%
“…Physical fitness is a strong health marker in the general population [20] and in other rheumatologic diseases including rheumatoid arthritis [21] and fibromyalgia [2224], among others. It has been reported that patients with SLE present a reduced cardiorespiratory fitness (CRF) [4–7,25], muscular strength and functional capacity [26]. Functional aerobic impairment [6,25] and low levels of strength [26] in SLE are negatively correlated with perception of severity [6], fatigue [6,26], and age-related arterial stiffness [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients with SLE present a reduced cardiorespiratory fitness (CRF) [4–7,25], muscular strength and functional capacity [26]. Functional aerobic impairment [6,25] and low levels of strength [26] in SLE are negatively correlated with perception of severity [6], fatigue [6,26], and age-related arterial stiffness [25]. Furthermore, a fitness level below the criterion-referenced standards could lead to a premature loss of independence [27].…”
Section: Introductionmentioning
confidence: 99%